Investigation of Biomass Ash Properties for Their Utilization Assesment (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Ash is a mineral waste group, which quantity increases on a global scale and now it has achieved hundreds of millions of tons, and as they are an integral part of the any solid fuel, including biomass the production rate will continue. At the same time ash, due to their nature and composition is a unique material that can be valuable technogenic resource. The paper studies the wood ash physical properties (density, porosity, specific free surface) composition and the metal adsorption ability. It was found that wood ash contains a significant percentage of metals in the mobile phase, which dissolve in the water and thus are able to spread into the surrounding soil. The study established a high adsorption activity of ash (95-99%) to the metals. It was found that the adsorption capacity of the ash is possible to increase with the activation of the ash particle surfaces and changing the pore structure.